STUDI KUALITATIF DUKUNGAN SUAMI DALAM PEMANFAATAN PELAYANAN ANTENATAL CARE (ANC) DI PUSKESMAS TANARA KABUPATEN SERANG - Shiva Nabilah; Dewi Purnamawati; Tria Astika; Toha Muhaimin; Fatimah (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
Background: This study aims to obtain in-depth information about deep-husband support Utilization of Antenatal Care (ANC) services at the Tanara Health Center District. Method: This study uses a qualitative method with a phenomenological approach. This research was conducted in the working area of ​​the Tanara Public Health Center, Serang Regency, involving 11 informants which were divided into 5 key informants and 6 supporting informants. The sampling technique used to determine the informants for this study was purposive sampling. This research was conducted for one month from January 2023 to February 2023. The research data was obtained through observation, interviews, and documentation studies. Then, the data obtained were analyzed using reduction techniques, data presentation, and drawing conclusions which were then validated using source and technique triangulation methods.